Penerapan Data Mining Menggunakan Algoritma K- Nearest Neighbor untuk Penentuan Penerimaan Proposal Hibah - Widaningsih, Sri; Suheri, Agus; Fauziyana, Tiara Tsaniya (Universitas Suryakancana, 2024)
The grant program for farmers is one of the government programs provided by the Cianjur Regency Agriculture Office. To accept the program, farmers submit proposals which will be reviewed by the proposal reviewer analyst. In making a decision to accept a grant proposal, it is necessary to make a quick and accurate decision. With quite a lot of proposal data that has been submitted, it can be used data patterns that have been stored with data mining methods to predict proposals that are accepted with proposals that are rejected. The algorithm used is K-Nearest Neighbor where the determination of acceptance of new proposal data is based on the closest distance to the acceptance of the previous proposal. There are six predictor variables used, namely assets, capital, business scale, length of business, cost plan and completeness of documents. The stages of data mining use the stages in Knowledge Discovery in Databases (KDD). Calculations use the weight of the assessment for each proposal criteria that have been determined. The results of the evaluation of the calculation of the kNN algorithm obtained a real accuracy of 76% and an error rate of 24%. From the calculation results, the kNN algorithm can be used as a model to determine recipients of agricultural grant programs. Program pemberian dana hibah untuk para petani merupakan salah satu program pemerintah yang diberikan oleh Dinas Pertanian Kabupaten Cianjur. Untuk menerima program tersebut petani mengajukan proposal yang akan diperiksa oleh analis pemeriksa proposal. Dalam mengambil keputusan penerimaan proposal hibah perlu adanya keputusan yang cepat dan akurat. Dengan cukup banyaknya data proposal yang telah diajukan , maka dapat digunakan pola data yang telah tersimpan dengan metode data mining untuk memprediksi proposal yang diterima dengan proposal yang ditolak. Algoritma yang digunakan yaitu K-Nearest Neighbor di mana penentuan penerimaan data proposal baru berdasarkan pada jarak terdekat dengan penerimaan proposal sebelumnya. Terdapat enam variabel prediktor yang digunakan yaitu aset, modal, skala usaha, lama usaha, rencana biaya dan kelengkapan dokumen. Tahapan data mining menggunakan tahapan dalam knowledge Discovery in Databases (KDD) . Perhitungan menggunakan bobot penilaian untuk setiap kriteria proposal yang sudah ditentukan. Hasil evaluasi perhitungan algoritma kNN diperoleh akurasi sebenar 76% dan tingkat error sebesar 24%. Dari hasil perhitungan, algoritma kNN ini dapat digunakan sebagai model untuk menentukan penerima program hibah pertanian.